Every day is exciting ebook - Jules, Jacqueline (Sofia Martinez., 2018)
When Sofia is around, every moment of every day is exciting. This spunky 7-year-old can even make having the hiccups fun! Can you imagine what kind of fun Sofia will have at her first quinceañera or when the lights go out? No matter what happens, it will be memorable if Sofia is involved! This early chapter book from the Sofia Martinez series includes Spanish words in the text and a Spanish glossary.